2010
DOI: 10.1051/0004-6361/201015194
|View full text |Cite
|
Sign up to set email alerts
|

Fast ray-tracing algorithm for circumstellar structures (FRACS)

Abstract: Context. B[e] supergiants are luminous, massive post-main sequence stars exhibiting non-spherical winds, forbidden lines, and hot dust in a disc-like structure. The physical properties of their rich and complex circumstellar environment (CSE) are not well understood, partly because these CSE cannot be easily resolved at the large distances found for B[e] supergiants (typically > ∼ 1 kpc). Aims. From mid-IR spectro-interferometric observations obtained with VLTI/MIDI we seek to resolve and study the CSE of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The CO bandhead emission, which has a higher line-to-continuum Notes. As discussed in Domiciano de Souza et al (2011), the uncertainties reported by the Levenberg-Marquardt algorithm should be considered lower limits to the actual uncertainty in the best fitting parameters. The sizes in AU and R were calculated assuming a distance of 1500 pc.…”
Section: Brγ and Co Visibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO bandhead emission, which has a higher line-to-continuum Notes. As discussed in Domiciano de Souza et al (2011), the uncertainties reported by the Levenberg-Marquardt algorithm should be considered lower limits to the actual uncertainty in the best fitting parameters. The sizes in AU and R were calculated assuming a distance of 1500 pc.…”
Section: Brγ and Co Visibilitiesmentioning
confidence: 99%
“…Domiciano de Souza et al 2011). However, it has been shown that simple models of the dust emission from equatorial disks struggle to simultaneously reproduce the spectral energy distribution of the sgB[e] star R126 in the optical/near infrared (NIR) and the mid infrared (Porter 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The technique of spectrally resolved optical interferometry (spectro-interferometry) is used in astronomy to deliver high-resolution images of astronomical targets and study their morphological features [1]. To this end, measurements of the visibility and phase (complex visibilities) of interference fringes obtained by combining simultaneously light collected by several distant telescopes are required.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution spectro-interferometry assisted by model imaging can deliver further insights in the dynamical structure of astrophysical objects [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the huge potential of the AMBER instrument has been already proved by the numerous first articles published in a special feature of A&A Tatulli et al 2007a;Meilland et al 2007b,a;Weigelt et al 2007;Millour et al 2007;Chesneau et al 2007;Domiciano de Souza et al 2007), and many other new successful observing programs can be expected for the future, even with the infrastructure-limited performances of the instrument.…”
Section: Resultsmentioning
confidence: 99%